NICKEL MINING CONCESSIONS FOR THE ELECTRIC VEHICLE INDUSTRY IN INDONESIA FROM AN ENVIRONMENTAL LAW PERSPECTIVE - Mukhlis Mukhlis; Dominikus Rato; Bayu Dwi Anggono (Universitas Trunodjoyo Madura, 2024)
Indonesia as a developing country is actively pursuing strategic policies to bring about change to become a more advanced country. One of its main initiatives is to utilize abundant natural resources, especially through nickel concessions, with the aim of positioning Indonesia as a center for the electric vehicle industry. However, the implementation of these policies often shows deviations in compliance with regulations, technical practices in the field, and aspects of humanitarian rights enshrined in the constitution. Although the goal is to minimize environmental damage, deviations in regulations and technical implementation often occur. Achieving balance is critical, emphasizing environmental preservation and citizens' inherent right to life. Effective execution requires the government to consistently comply with applicable laws and regulations in Indonesia. In addition, strict supervision of private entities involved in nickel mining concessions on important lands is essential. This monitoring ensures environmental sustainability and encourages the realization of sustainable development goals. The government's commitment to environmental protection must be in line with humanitarian principles, and not ignore the welfare of communities affected by nickel mining activities. Achieving a harmonious balance between economic development and ecological conservation is paramount. Therefore, the government must strengthen its regulatory framework, strengthening the legal basis that guides this strategic initiative. Indonesia's journey towards becoming a developed country depends on its ability to face the challenges posed by the nickel industry. Prioritizing environmental conservation and respecting citizens' rights are non-negotiable elements in this progress. By enforcing and strengthening the regulatory framework, the government can not only ensure sustainable development but also encourage a responsible and ethical approach to utilizing the country's natural resources.